2020
DOI: 10.1142/s0192415x20500688
|View full text |Cite
|
Sign up to set email alerts
|

Corni Fructus as a Natural Resource Can Treat Type 2 Diabetes by Regulating Gut Microbiota

Abstract: Accumulating evidence suggests that gut microbiota plays a crucial role in the development of metabolic diseases, especially type 2 diabetes mellitus (T2DM). The nutrient-rich resource Cornus Fructus (CF) showed curative effects on diabetes mellitus. However, the mechanism underlying its hyperglycemic activity remains obscure. Herein, the antidiabetic potential of four extracts from CF, including saponin (CTS), iridoid glycoside (CIG), tannin (CT), and alcohol extract (CCA) was evaluated in vivo. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… Zhang et al (2021c) demonstrated that the RR-CO combination remarkably increased the abundance and diversity of GM in rats with adenosine-induced chronic kidney disease. CO extract selectively modulated the structure of GM, thereby alleviating T2DM ( Niu et al, 2020 ). Qin-xin-tang increased the SCFA-producing flora in the gut of T2DM rats, thus, up-regulating the secretion of SCFA, increasing intestinal integrity, inhibiting inflammatory response, and improving insulin resistance ( Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Zhang et al (2021c) demonstrated that the RR-CO combination remarkably increased the abundance and diversity of GM in rats with adenosine-induced chronic kidney disease. CO extract selectively modulated the structure of GM, thereby alleviating T2DM ( Niu et al, 2020 ). Qin-xin-tang increased the SCFA-producing flora in the gut of T2DM rats, thus, up-regulating the secretion of SCFA, increasing intestinal integrity, inhibiting inflammatory response, and improving insulin resistance ( Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Chen et al (2018) reported that the Huang-Lian-Jie-Du-Decoction ameliorated hyperglycemia and restored the dysregulated microbiota structure and function, mainly by increasing short chain fatty acid (SCFA)-producing bacteria and reducing conditioned pathogenic bacteria in T2DM rats. Extracts of CO have been demonstrated to exhibit curative hypoglycemic effects and selectively modulate GM in T2DM mice ( Niu et al, 2020 ). Zhang et al (2021c) implied that GM and their metabolites might play a vital role in the progression of chronic kidney disease, which was reversed by the treatment with Rehmannia Radix Preparata and CO herb pair.…”
Section: Introductionmentioning
confidence: 99%
“…Niu D et al. ( 100 ) intervened with Cornus officinalis extract in T2DM mice, improving glucose and lipid metabolism disorders and upregulating the secretion of GLP-1 and GLP-2. They also alleviated T2DM symptoms by upregulating the abundance of Gram positive bacteria (Lactobacillus, Clostridium, etc.)…”
Section: Study On the Mechanism Of Tcm Intervention On Dm By Regulati...mentioning
confidence: 99%